ANALISIS DAYA LEDAK, KESEIMBANGAN DAN KOORDINASI TERHADAP KEMAMPUAN MENENDANG BOLA PADA PERMAINAN SEPAKBOLA MURID SDN PACINONGAN UNGGULAN KABUPATEN GOWA - Ahmad Adil (Program Studi Ilmu Keolahragaan, 2023)
This research aims to obtain answers to problems: (1). Is there a contribution of leg explosive power to the ability to kick the ball in a soccer game? (2). Is there a contribution of balance to the ability to kick the ball in a soccer game? (3). Is there a contribution of eye-foot coordination to the ability to kick the ball in a soccer game? (4). Is there a joint contribution of leg explosive power, balance and eye-foot coordination to the ability to kick the ball in a soccer game? This research is descriptive of three independent variables and one dependent variable. The population and sample were students at SDN Pacinongan Unggulan and by random sampling a sample of 60 people was obtained. The data analysis technique used was correlation (R-test). Based on the results of data analysis, it can be concluded as follows: (1). There is a significant contribution of leg explosive power to the ability to kick the ball in a soccer game, where the value of Ro = 0.596 (P < 0.05). with a contribution of 0.755 which means 75.50%. (2). There is a significant contribution of balance to the ability to kick the ball in soccer games, where the value of Ro = 0.761 (P < 0.05). with a contribution of 0.713 which means 71.30% (3). There is a significant contribution of eye-foot coordination to the ability to kick the ball in a soccer game, where the value of Ro = 0.866. (P < 0.05). with a contribution of 0.820 which means 82.00%. (4). There is a significant joint contribution of leg explosive power, balance and eye-foot coordination to the ability to kick the ball in a soccer game, where the value of Ro = 0.928. which contributed 0.829 which means 82.90%.